English Language Book Reading Based on Contextu- al Teaching and Learning (CTL) for Elementary School Students - Usman, Herlina; Lestari, Ika; Anisah, Anisah; Nuf Fadhillah, Dini; Iasha, Vina (Opción, 2019)
This study aims to describe the use of English language book reading based on contextual teaching and learning for elementary school students. This re- search used a qualitative approach. This study collaboration with 25 students in 5th grade and 2 English teachers through interviewed for 40-45 minutes at 24 Muhammadiyah elementary school, Rawamangun, Jakarta, Indonesia. Data collection was also carried out by documentation of basic reading com- petency standards for 5th grade elementary school. The results of this study indicate that the existence of English language book reading based on contex- tual teaching and learning increases students ‘interest in reading, motivates students to learn and read English, and increases students’ interest in learn- ing English. In addition, English language reading books make it easier for teachers to support students’ reading competencies and introduce students to English language especially vocabulary material.